UJI EFEKTIFITAS BEBERAPA ENTOMOPATOGEN PADA IMAGO PENGGEREK BUAH KAKAO Conopomorpha cramerella Snellen (Lepidoptera: Gracillariidae) Di LABORATORIUM - Yusuf Sugianto; Yuswani Pangestiningsih; Syahrial Oemry (Jurnal Agroekoteknologi, 2013)
The effectivity of some entomopathogenic imago cocoa fruit borerConopomorpha cramerella Snellen (Lepidoptera: Gracillariidae) in the Laboratory. Theobjective of this research was to evaluate the effectifity of entomophatogen (B. bassiana,M. anisopliae and P. fumosoroseus) with different concentration level. The experiment wasconducted at the Laboratory Plant Pests, Faculty of Agriculture, University of Sumatra utara,Medan. From August to October 2012, using a completely randomized design (RAL) nonfactorial of 7 treatments and 3 replications. The treatments were L0 (control),L1 (M. anisopliae 40gr/1l), L2 (M. anisopliae 50gr/1l), L3 (B. bassiana 40gr/1l),L4 (B. bassiana 50gr/1l), L5 (P. fumosoroseus 40gr/1l), and L6 (P. fumosoroseus 50gr/1l).The results showed that 50gr/1l M. anisopliae is effective to control imago C. cramerella(100%), followed by treatments B. bassiana 50gr/1l, M. anisopliae 40gr/1l, andP. fumosoroseus 50gr/1l, the high number of imago C. cramerella overgrownentomopathogenic fungus colony found in 50gr/1l M. anisopliae (60%), followed bytreatments of P. fumosoroseus 50gr/1l, M. anisopliae 40gr/1l, B. bassiana 50gr/1l,B. bassiana 40gr/1l, while P. fumosoroseus 40gr/1l is less effective, and the behavior of deathimago C. cramerella entomopathogenic fungus infected seen with characteristic imago beinglazy move, the longer the body becoming limp and dead, and that eventually hardenedmycelium covered by different colors namely M. anisopliae has green colour, B. bassiana haswhite colour, P. fumosoroseus has yellowish white colour.Keywords : entomopathogenic, cocoa, Conopomorpha cramerella